TEORI KODE-KODE BERBICARA - Pala, Rukman (Istek Widuri Jakarta, 2014)
This article substantive describes The Theory of Speaking Codes from Gerry Philipsen. Briefly, these include background birth of the theory; the substance of Speaking Code Theory; shape/appearance of ethnography; criticism of the theory; and conclusion. The discussion showed that one of the five core theory is related to the arguments stated in the form of propositions, that “where there is a cultural difference, there will be found different speaking code